Population homogeneity with unequal exploitation and recruitment contribution within the 2700 km geographic distribution of the commercial hairy crab Romaleon setosum (Decapoda: Cancridae) in Chile - Branco Tubin-Arenas; Noemi Rojas-Hernández; Ciro Rico; Caren Vega-Retter; Luis Miguel Pardo; David Veliz (PLoS ONE, 2025)
Knowledge of the genetic structure of commercially exploited marine species populations is crucial to gaining insights into stock dynamics and population connectivity. This information is essential for effective fisheries management. Economically important benthic fishery species include brachyuran crabs, with the hairy crab Romaleon setosum being an important resource in Chile and Peru. The exploitation is uneven along the Chilean coast, with two areas accounting for 67% of the total biomass caught per year. The genetic structure of the R. setosum population along the Chilean coast was analysed based on the variability of thousands of single-nucleotide polymorphisms (SNPs) in individuals from 10 areas covering 2700 km of coastline. After data filtering, 256 individuals and 2,383 SNPs remained. There was no evidence of genetic population structure within the studied area, suggesting that there is only one genetic population of R. setosum along the coast of Chile. Therefore, among Cancridae species, R. setosum has the largest geographic distribution of a single population described worldwide to date. Finally, the analysis of gene flow showed that the zone with the highest fishery also provided the highest proportion of migrants to the other zones. This study emphasises the urgency of local management of source populations in conjunction with the use of size and sex for fisheries control of R. setosum along the Chilean coast.